Indian tourism : diaspora perspectives - Chowdhary, Nimit; Billa, Suman; Tiwari, Pinaz (Emerald Publishing Limited, 2022)
Indian Tourismbrings together leading experts from all over the world to assess the challenges and opportunities of the tourism sector in India and its correlation to the country's economic performance and prospects.